2020
DOI: 10.1093/jnci/djaa204
|View full text |Cite
|
Sign up to set email alerts
|

Germline Cancer Predisposition Variants inPediatric Rhabdomyosarcoma: A Report From the Children’s Oncology Group

Abstract: Background Several cancer-susceptibility syndromes are reported to underlie pediatric rhabdomyosarcoma (RMS); however, to our knowledge there have been no systematic efforts to characterize the heterogeneous genetic etiologies of this often-fatal malignancy. Methods We performed exome-sequencing on germline DNA from 615 patients with newly diagnosed RMS consented through the Children’s Oncology Group. We compared the prevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
91
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 72 publications
(94 citation statements)
references
References 43 publications
3
91
0
Order By: Relevance
“…Although our case harbors wildtype DICER1, which was con rmed by whole-exome and Sanger sequencing, DICER1 mutations have been reported in both primary CNS and non-CNS rhabdomyosarcoma [8][9][10][11]17]. A case of primary CNS rhabdomyosarcoma with NF1 was also reported, and an association between NF1 and non-CNS rhabdomyosarcoma is known [18][19][20]. We then further revealed the demographic similarities between CNS and non-CNS rhabdomyosarcoma.…”
Section: Discussionmentioning
confidence: 51%
“…Although our case harbors wildtype DICER1, which was con rmed by whole-exome and Sanger sequencing, DICER1 mutations have been reported in both primary CNS and non-CNS rhabdomyosarcoma [8][9][10][11]17]. A case of primary CNS rhabdomyosarcoma with NF1 was also reported, and an association between NF1 and non-CNS rhabdomyosarcoma is known [18][19][20]. We then further revealed the demographic similarities between CNS and non-CNS rhabdomyosarcoma.…”
Section: Discussionmentioning
confidence: 51%
“…The presence of pathogenic germline variants was not significantly associated with age (mean 10.9 vs. 10.5 years, p = 0.42 by twosided t-test) or sex (p = 0.81 by Fisher's exact test). Across the pan-sarcoma discovery cohort, nominal enrichment signal at p < 0.05 was observed for multiple genes previously implicated in sarcoma pathogenesis, including TP53, NF1, and DICER1 5,18,25 ; nominal enrichment signal was also seen for MUTYH, PALB2, NTHL1, and FANCC, genes with less prior supporting evidence for their role in sarcoma germline predisposition. The enrichment in TP53 was greatest, reaching significance at FDR < 0.05 across the pan-sarcoma discovery cohort (Figure 2B; Table S7).…”
Section: Pathogenic Germline Variants In Cancer Predisposition Genes Are Enriched Across Pediatric Sarcoma Histologic Subtypes Relative Tmentioning
confidence: 97%
“…Two such RMS-specific cohort sequencing studies have recently explored both the frequency and identity of germline mutations in cancer predisposition genes in RMS patients. Our group completed the Genetics of Embryonal and Alveolar Rhabdomyosarcoma Study (GEARS), which performed germline WES analysis of 615 RMS patients from the Children’s Oncology Group in order to determine the prevalence of germline mutations in 70 known cancer predisposition genes [ 99 ]. We found that 45 of the 615 patients (7.3%) possessed cancer predisposition germline mutations.…”
Section: Large-scale Pediatric Cancer Germline Genetics Studiesmentioning
confidence: 99%